Pelatihan Pengenalan Jenis Vitamin-D Dan Penghitungan Dosis Vitamin-D Yang Tepat Untuk Lansia - Joice Viladelvia Kalumpiu; Kurniasari; Erita Istriana; Kartini; Triasti Khusfiani; Jane Florida Kalumpiu (CV. Multi Kreasi Media, 2024)
Vitamin D is a nutrient known to play an important role in maintaining healthy bones and the immune system, and has a significant impact on the physical and mental health of older adults. Lack or excess of vitamin D can have an impact on the health of the elderly. In this PKM program, training will be provided regarding the introduction of types of vitamin D and calculating the correct dose of vitamin D for the elderly. This PKM was held at the RPTRA of Krendang Subdistrict, Tambora, West Jakarta, on March 7th 2024. The activity began with welcoming remarks by the subdistrict, registration, filling out questionnaires, training, question and answer, giving souvenirs and foods. In this program, 33 elderly attended, and the majority were women. Most elderly do not know about vitamin D. It is hoped that this training can provide good information and understanding about the importance of vitamin D and how to consume it properly.